Epidemiological characterization of isolates of Salmonella enterica and shiga toxin-producing Escherichia coli from backyard production system animals in the Valparaíso and metropolitana regions - Urzúa-Encina, Constanza; Fernández-Sanhueza, Bastián; Pavez-Muñoz, Erika; Ramírez-Toloza, Galia; Tomazic, Mariela Luján; Rodriguez, Anabel Elisa; Alegría-Morán, Raúl (MDPI, 2024)
Backyard production systems (BPS) are distributed worldwide, rearing animals recognized as reservoirs of Salmonella enterica and Shiga toxin-producing Escherichia coli (STEC), both zoonotic pathogens. The aim of this study was to characterize isolates of both pathogens obtained from animals raised in BPS from two central Chile regions. The presence of pathogens was determined by bacterial culture and confirmatory PCR for each sampled BPS, calculating positivity rates. Multivariate logistic regression was used to determine risk factors. Additionally, phenotypic antimicrobial resistance was determined. A positivity rate of 2.88% for S. enterica and 14.39% for STEC was determined for the complete study region (Valparaíso and Metropolitana regions). Risk factor analysis suggests that the presence of ruminants (OR = 1.03; 95% CI = 1.002–1.075) increases the risk of STEC-positive BPS, and the presence of ruminants (OR = 1.05; 95% CI = 1.002–1.075) and the animal handlers being exclusively women (OR = 3.54; 95% CI = 1.029–12.193) increase the risk for S. enterica/STEC positivity. Eighty percent of S. enterica isolates were multidrug resistant, and all STEC were resistant to Cephalexin. This study evidences the circulation of multidrug-resistant zoonotic bacterial strains in animals kept in BPS and the presence of factors that modify the risk of BPS positivity for both pathogens.